Improving Students’ Potential in Translation Skills from Thai into English through CRRU English Broadcast Channel - Kantamas, Kannikar; Wangmanee, Preeyapha; Jitpranee, Jutharat (Ratchaphruek Journal, 2023)
The study employed a participatory action research method by collecting data from 3 volunteered villages in Chiang Rai that are ready to develop their international potential with representatives in each village leader, two OTOP products, and 31 English Studies major students in 3rd year (International Major) who had registered and enrolled in the course called, “English for Mass Media”. The instruments were news scripts in Thai and English and students’ satisfaction questionnaires. Data were analyzed by using mean ( ), standard derivation (S.D.), and content analysis. Findings revealed that 1) students translated the news and activities of the villages according to the concept of Pimpan Vessakosol (2012), referring to using transliteration, having the same meaning, similar meaning, having more explanation, and using direct translation. 2) students were highly satisfied with the activities of the study, and 3) the research team presented the advertisement through Facebook Live which was recorded online on the Chiang Rai Rajabhat University YouTube channel with the keyword “CRRU English Broadcast”. This study has 3 purposes, including 1) to improve students’ potential in translation skills from Thai into English; 2) to study students’ potential in translation skills from Thai into English through CRRU English Broadcast activities, and 3) to promote news and activities of the local villages in Chiang Rai Province to international contexts.